(untitled) (Global Journal of Science Frontier Research, 2017)
Most of the gelada baboon’s population which is endemic to Ethiopia exists on the gorges and mountain cliffs of the country including Debre-Libanos. The objective of the study was to estimate the total gelada baboons, and determine their group size and age structure. This was investigated based on direct field observation method from August 2012 to March 2013. The study area was divided into seven counting blocks (Shinkurt Mikael, Chagel, Amanuel, Abba Dinkona, Wusha Gedel, Tekle Haimanot, and Set Debre). Data were analyzed using descriptive statistics. Chi-square test was used to compare the sex and age ration, and their distribution among the counting blocks. The population size of gelada baboons was determined from direct total count. The average number of gelada baboons counted was 1608. Of these, adult males comprised 162, adult females 576, sub-adult males 121, sub-adult females 231, young 307 and infants 212. There was a significant difference among the different age groups of the total individuals counted in the study area (χ2=1002.657, df=5, p